ASPECTOS RELACIONADOS À ESCOLHA DO TIPO DE PARTO: um estudo comparativo entre uma maternidade pública e outra privada, em São Luís, Maranhão - Mandarino, Natália Ribeiro (2008)
This study aimed to analyze some aspects related to the choice of the type of delivery and assess the rates of caesarean sections in two referral maternity hospitals, a public and a private one, in São Luís, State of Maranhão, Brazil. Through a cross-sectional study, 163 primiparous women at the public maternity and 89, at the private one, with medium ages of 21,63 ± 5,24 e 28,8 ± 5,41 years respectively, admitted consecutively, were aborded. In the antepartum period, the women were asked about their preference in regard to the manner of giving birth: via vaginal or by caesarean section. In the postpartum period it were obtained informations about social-demographic data, prenatal care, the type of delivery accomplished and women s satisfaction with each type, and the indications for the caesarean sections, being made an univariated comparision between the two samples. The statistical analyze was processed in the Epi-info program, being considered significant a p < 0,05. There were more brown women at the public hospital e more white ones at the private maternity. At the private maternity it was observed too a better level of scholarship and income. In regard to the type of delivery, 79,1% of the childbearings at the public maternity said to prefer the vaginal way, while the majority (67,4%) of the private unit women expressed their preference for the caesarean section (p < 0,0001). In the two groups, the majority of the women related to have received prenatal care (96,9 and 98,9%, respectively), being complete in 57% and 97,8% of the childbearings, respectively. The caesarean section was accomplished in 46% of the women at the public maternity and in 97,8% of those ones attended at the private maternity (p< 0,0001), being registered a medical indication in 94,7% and 63,2% of the cases, respectively (p< 0,0001); in the private unit, the remaining 36,8% cases were ascribed to maternal request . The main indications for caesarean section at the public maternity were cephalo-pelvic disproportion (39,4%), pregnancy-induced hypertension (29,6%) and foetal distress (25,4%), and at the private one, cephalo-pelvic disproportion 45,5%), fetal distress (27,3%) and pregnancy-induced hypertension (21,8%). The satisfaction rate of the women was high with both types of delivery, at both maternities, but the intention to repeat the type of delivery was more frequently reported among those ones submitted to a vaginal delivery (71,6 x 41,3%, at the public, and 100 x 65,5%, at the private maternity). Among the childbearings assisted at the public hospital, the caesarian subgroup presented a higher proportion of whites and women with better income. So, in the present study, caesarean sections rates were elevated in both public and private maternities, but significantly higher at the private one, where it was observed too a higher proportion of caesarian sections ascribed to maternal request . It was evidenced yet a higher preference for vaginal delivery at the public maternity and for caesarian section at the private one. White race and better income were significantly associated with the occurence of caesarean sections at the public maternity.